RISET APLIKASI KESELAMATAN KEBAKARAN DI KAPAL - Ariany, Zulfaidah (Vocational School Diponegoro University, 2011)
Zulfaidah Ariany, in this paper explain that fire ship at sea is a dangerous thing, both on the ship itself or on its passengers. Crew boat had put out the fire without the help of other collateral. Without a good extinguishing system will certainly result in damage to the ship and would endanger the safety of the soul crew and passenger ships.Ship fire safety research conducted by various parties including government organizations and non governmental organizations and academic institutions related to fire safety aspects of shipping and ship.The need for revision of regulations that have been enacted sail for this through the provision of research. Research conducted to gain understanding of the dangers that may occur on the ship, and a good method for controlling and extinguishing the fire. Research that was conducted earlier used as a basis in research notes or to come.Â Keywords : ship fire, fire safety